2013
DOI: 10.3109/10641955.2013.837175
|View full text |Cite
|
Sign up to set email alerts
|

The association of circulating angiogenic factors and HbA1c with the risk of preeclampsia in women with preexisting diabetes

Abstract: Objective:To assess whether glycemic control, soluble fms-like tyrosine kinase 1 (sFlt1) and placental growth factor (PlGF) were associated with the development of preeclampsia (PE) or gestational hypertension (GHTN) in women with preexisting diabetes.Methods:Maternal circulating angiogenic factors (sFlt1 and PlGF) measured on automated platform were studied at four time points during pregnancy in women with diabetes (N = 159) and reported as multiples of the median (MOM) of sFlt1/PlGF ratio (median, 25th–75th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 35 publications
4
31
1
Order By: Relevance
“…In our study, frequency of preeclampsia was 33 %, which is almost 3 times more frequent than reported 12 % in other studies (11,12).…”
Section: Discussioncontrasting
confidence: 46%
“…In our study, frequency of preeclampsia was 33 %, which is almost 3 times more frequent than reported 12 % in other studies (11,12).…”
Section: Discussioncontrasting
confidence: 46%
“…Smaller longitudinal studies have examined these markers in women with type 1 diabetes who did not have microalbuminuria in early pregnancy [32], women with preexisting diabetes that required insulin [33], and a mixed group of women with type 1 or type 2 diabetes [34]. sFlt-1, sEng and PGF prior to 25 weeks gestation did not differ between diabetic women who developed preeclampsia and those who did not [34, 32, 33].…”
Section: Preeclampsia In Women With Type 1 or Type 2 Diabetesmentioning
confidence: 99%
“…sFlt-1, sEng and PGF prior to 25 weeks gestation did not differ between diabetic women who developed preeclampsia and those who did not [34, 32, 33]. After 25 weeks gestation, results were conflicting.…”
Section: Preeclampsia In Women With Type 1 or Type 2 Diabetesmentioning
confidence: 99%
“…Previous studies have shown that women with good blood glucose control, both prior to and during pregnancy, are at a reduced risk of pre-eclampsia, compared to those with poor glycaemic control (Cohen et al, 2014;Holmes et al, 2011). Despite this, the majority of women in the current study did not recall receiving information about the benefits of good glycaemic control on the risk of pre-eclampsia.…”
Section: Discussionmentioning
confidence: 60%